Characterization of Dust Accumulation and Its Effect on the Performance of Photovoltaic Cells - Qaisieh, Alaa Moh’d (2022)
A Master of Science thesis in Mechanical Engineering by Alaa Moh’d Qaisieh entitled, “Characterization of Dust Accumulation and Its Effect on the Performance of Photovoltaic Cells”, submitted in November 2022. Thesis advisor is Dr. Bassam A. Abu-Nabah and thesis co-advisor is Dr. Mohamed Hamdan. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).